Playing with your mind - Rodriguez, Mauro (2013)
A Brain-Computer Interface (BCI) is a communication system between the brainand a machine like a computer. Some BCI systems have been used to help people withdisabilities and sometimes, with entertainment purposes. In this paper, a BCI-game system is developed. It allows controlling the altitude of a ball inside of a glass pipe according to mental concentration level, which is measured on EEG signals of the user. The system is automatically adjusted to each user, hence, it is not needed any calibration step. Ten subjects participated in the experiments. They achieved effective control of the ball in a few minutes, demonstratingthe feasibility of the BCI-game system.